Factors Associated with Hyposalivation in Brazilian Adults - de Carvalho, Handerson Nunes (2023)
Objective: To determine the occurrence of hyposalivation in Brazilian adults and its association with individual determinants, such as the use of medications, systemic conditions, smoking, and alcohol consumption. Material and Methods: A cross-sectional study with 402 adults was developed. Information was collected on sociodemographic and general health characteristics, and sialometry was performed with stimulated salivary flow. It indicated low salivary flow when ≤ 0.7 mL/min. Bivariate and multivariate analyses were conducted using a decision tree (p<0.05). Results: The sample was comprised predominantly of women (68.2%) aged ≤ 29 years (25.4%). Most participants did not use medication (56.7%). Among systemic diseases, the most cited was hypertension (25.1%). More than a third of the participants presented hyposalivation (40.3%), being associated with the following variables: age between 50 to 59 years (p=0.011), female sex (p<0.001), menopause (p=0.001), use of alcohol (p=0.033), systemic disease (p=0.002) and medication use (p<0.001). In multivariate analysis, in addition to sex (p<0.001) and hypertension (p=0.005), an association was also found between hyposalivation and diabetes (p=0.014). Conclusion: Factors associated with hyposalivation in adults were sex and the presence of hypertension or diabetes.